A History of Horror, 2nd Edition - Dixon, Wheeler W., 1950-; Project Muse. (London : Rutgers University Press, 2023)
"Ever since horror leapt from popular fiction to the silver screen in the late 1890s, viewers have experienced fear and pleasure in exquisite combination. Wheeler Winston Dixon's fully revised and updated A History of Horror is still the only book to offer a comprehensive survey of this ever-popular film genre. Arranged by decades, with outliers and franchise films overlapping some years, this one-stop sourcebook unearths the historical origins of characters such as Dracula, Frankenstein, and the Wolfman and their various incarnations in film from the silent era to comedic sequels. In covering the last decade, this new edition includes coverage of the resurgence of the genre, covering the swath of new groundbreaking horror films directed by women, Black and queer horror films, and a new international wave in body horror films. A History of Horror explores how the horror film fits into the Hollywood studio system, how the distribution and exhibition of horror films have changed in a post-COVID world, and how its enormous success in American and European culture expanded globally over time. Dixon examines key periods in the horror film-in which the basic precepts of the genre were established, then banished into conveniently reliable and malleable forms, and then, after collapsing into parody, rose again and again to create new levels of intensity and menace. A History of Horror, supported by rare stills from classic films, brings over sixty timeless horror films into frightfully clear focus, zooms in on today's top horror Web sites, and champions the stars, directors, and subgenres that make the horror film so exciting and popular with contemporary audiences"--
Origins : 1896-1929 -- Classics : 1930-1948 -- Rebirth : 1949-1970 -- New blood : 1970-1990 -- The next wave : 1990-2010 -- Into the future : 2010-present.
Print version record.
Includes bibliographical references (pages 245-251) and index.
JSTOR
Keywords: Motion pictures -- History; Horror films -- History and criticism; Cinéma -- Histoire; Films d'horreur -- Histoire et critique; PERFORMING ARTS / General; Horror films; Motion pictures; Horror movies, horror flicks, horror films, michael myers, freddy krueger, Dracula, Frankenstein, film history, slasher movies, steven spielberg, directors, female directors, black directors, art, artists, picture film, horror movies near me, horror showings; Criticism, interpretation, etc; History